THE IDENTIFICATION OF PATIENTS’ NEEDS TOWARD PHARMACY SERVICES IN SAMARINDA, INDONESIA– A CROSS-SECTIONAL STUDY - Sylvan Septian Ressandy (Universitas Muhammadiyah Kalimantan Timur, 2019)
Pharmacy supposed to be able to provide the services that accommodate all of the patient's needs. There are several factors to satisfy patients, such as product, price, process, and people. This research aims to patients’ needs toward pharmacy services to help the pharmacist satisfying the patients. The questionnaire composed of 8 items based on the marketing mix theory. Study took place in Samarinda, Indonesia from October to December 2018. There were 83 people responded to survey questions. Respondents’ answers counted by the Likert scale 1 until 5 and analyzed by ranking the mean score of each answer. Analysis from the questionnaire study showed that the highest patients’ needs toward pharmacy were a pharmacy that provides complete drugs (mean of 4.8313), complete drug labeling (4.7470), professional staff (4.6988) and affordable drug prices (4.5422).